PRINCIPLES OF OPTIMIZING CONTROL OF GAS TRANSPORTATION SYSTEMS UNDER CONDITIONS OF THEIR UNDERLOAD - Grudz, V. Ya.; Grudz, Ya. V.; Protsiuk, V. R.; Pidluskyi, V. P.; Portechyn, O. M.; Gershun, B. I. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2022)
The work is devoted to establishing the regularities of the flow of technological processes in gas transportation systems to optimize the operational management of operating modes under the condition of their incomplete loading. On the basis of the study of the stationary modes of operation of the gas transportation system with changes in the volume of gas pumping, the principle of building a mathematical model based on the superposition of the characteristics of linear sections and compressor stations is proposed, which makes it possible to estimate the throughput of the system, parameters of the operating mode, and energy consumption for gas transportation. The methods of building a system of integral influence coefficients for gas transportation systems in order to evaluate the parameters of its operation in stationary modes of operation are presented. Each change in the technological parameters of the operating mode at the entrance of the gas transport system will necessarily cause a reaction of the system, which will manifest itself in a change of the corresponding parameters at its exit. It is obvious that the input and output parameters of the system are interconnected by a complex system of equations, the implementation of which requires certain time costs and the collection of additional information about the technical and hydro-gas-dynamic conditions of the system at each moment of time. In the conditions of incomplete loading of the gas transportation system, which involves frequent changes in its operation modes, the implementation of the task is not always possible. It is proposed to create a system of integral influence coefficients that characterize the ratio of input and output information in various stationary modes and to formally present it in a matrix form. On the basis of the research results, the principle of optimizing the operation modes of the gas transportation system under conditions of partial loading according to the criterion of minimum energy consumption for gas transportation at the maximum level of gas supply reliability is proposed.